An investigation into efl learners' perceptions towards project-based learning in enhancing students’ english language communicative competence and twenty-first century skills at ud-ufls - Doan Thi Diem Hang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study examines the perceptions of 191 senior English-majored students and 82 students majored in English Language Teaching (ELT) programme at the University of Danang-University of Foreign Language Studies (UD-UFLS) towards how Project-based Learning (PBL) helps enhance their English language communicative competence and the 21st century skills. The research delves into the PBL approach and activities experienced by students, as well as the challenges they encounter during the learning process. The research has obtained the results that students generally have quite a positive attitude on PBL for improving language communicative competence, particularly in writing and speaking skills, as well as the 21st-century skills. Throughout their learning process, students have engaged in various types of PBL, however, encountered difficulties such as time management, workload, and maintaining motivation while participating in PBL activities